1995
DOI: 10.1016/0014-5793(94)01437-6
|View full text |Cite
|
Sign up to set email alerts
|

Cold denaturation of yeast phosphoglycerate kinase: which domain is more stable?

Abstract: Under destabilising conditions both heat and cold denaturation of yeast phosphoglycerate kinase (PGK) can be observed. According to previous interpretation of experimental data and theoretical calculations, the C-terminal domain should be more stable than the N-terminal domain at all temperatures. We report on thermal unfolding experiments with PGK and its isolated domains, which give rise to a revision of this view. While the C-terminal domain is indeed the more stable one on heating, it reveals lower stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Despite numerous studies of PGK's folding stability and dynamics (24)(25)(26) and the motion of its flexible hinge, by experiment (27) as well as by computation (28,29), it remains an open question to what extent the highly crowded environment can affect the PGK folding and structure and, ultimately, its enzymatic activity involving large-scale structural movement inside a cell. Although experimental studies using synthetic crowding agents have shown that the folding properties and enzymatic activity of simple proteins can be perturbed (30), our study shows that crowding leads to major conformational changes of PGK, with a major impact on its enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous studies of PGK's folding stability and dynamics (24)(25)(26) and the motion of its flexible hinge, by experiment (27) as well as by computation (28,29), it remains an open question to what extent the highly crowded environment can affect the PGK folding and structure and, ultimately, its enzymatic activity involving large-scale structural movement inside a cell. Although experimental studies using synthetic crowding agents have shown that the folding properties and enzymatic activity of simple proteins can be perturbed (30), our study shows that crowding leads to major conformational changes of PGK, with a major impact on its enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the wild-type yeast PGK used in the previous study contains two tryptophan residues. 43 Tryptophan 333 is buried in the main hydrophobic core. Its fluorescence is quenched strongly under native conditions.…”
Section: Experimental Designmentioning
confidence: 99%
“…38 -42 Cold-denatured PGK at low concentrations of denaturant (0.7 M guanidinium hydrochloride (GuHCl)) is nearly a random coil with a radius of gyration of 7.8 nm, and cold denaturation is an apparent two-state process. 42,43 Refolding of yPGK from all denatured states proceeds via a kinetic intermediate. 37 …”
Section: Phosphoglycerate Kinase Backgroundmentioning
confidence: 99%
“…yPGK is destabilized by lowering temperature 9,16,18,19 and such phenomenon can be evidenced by performing Gdn-HCl denaturation at various temperatures. By lowering temperature from 22°C to 4°C, a clear shift in the transition midpoint (Cm) value can be observed for GdnHCl induced transitions monitored either by ellipticity at 220 nm or by fluorescence ( Figs.…”
Section: Gdn-hcl Denaturation At Low Temperaturementioning
confidence: 98%
“…This finding is consistent with previously published studies suggesting that the C-terminal domain is more coldsensitive than the N-terminal domain. 19 Further information about the cold denaturation process can be obtained by using various Gdn-HCl concentrations. In particular, for denaturant concentrations lower that 0.6 M, the denaturation is not complete.…”
Section: Cold Denaturation Of Wild-type Ypgk and Ypgk ⌬404mentioning
confidence: 99%